Timing and Activation Intensity of Shoulder Muscles during Handball Penalty Throwing in Subjects with and without Shoulder Impingement - Zahra Zonnor; Nader Farahpour; Amirali Jafarnezhadgero (Vesnu Publications, 2017)
Introduction: Shoulder injuries are common among athletes in sports that involve overhead throwing of the ball such as handball. The objectives of this study were to evaluate the timing and activation intensity of shoulder muscles during handball penalty throwing in individuals with shoulder pain and in control subjects. Materials and Methods: Using BTS FREE EMG 300 system with bipolar surface electrodes, the timing (onset) and intensity of the activation of the shoulder muscles were measured including upper trapezius, anterior, middle and posterior deltoid, latissimus dorsi, pectoralis major, supraspinatus and triceps during penalty throwing. Multivariate analysis of variance (ANOVA) was used for between group comparisons with the significance level P< 0.05. Results: The activation intensity of upper trapezius and latissimus dorsi muscles in the healthy individuals were about 50.74% and 43.42% higher than in patients. Middle deltoid in healthy individuals was about 38.05% smaller than that in patients. In control group, supraspinatus muscle started earlier (23.5 ms) than the shoulder motion initiation. Triceps muscle was activated about 18.5 ms later than shoulder motion initiation. In patients, supraspinatus muscle started sooner (11 ms) and triceps brachialis muscle started later than the other muscles (22.16 ms). Conclusion: The coordination of shoulder muscles i.e. the onset and intensity of muscle activity is disturbed in the patient group during throwing. Hence, strength and stretching programs are recommended for athletes to reduce the risk of shoulder pain syndrome. The rehabilitation program can be focused on modifying the pattern of activity in upper trapezius, supraspinatus, latissimus dorsi and deltoid muscles in addition to pain control in the rehabilitation centers.